CRITICAL STUDY OF CRIMINAL SANCTIONS FOR CHILD NEGLECT BY PARENTS IN INDONESIA - Syahrin, M. Alpi (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2023)
Cases of child neglect are considered an indicator of the minimal quality of child protection in Indonesia. The law that is needed is criminal law because it is considered effective. Sanctions for perpetrators of criminal acts of child neglect are explained in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Criminal Provisions, Article 77B